Whole genome-based surveillance for human adenovirus-related diseases in Kobe City, Japan, 2018–2022 - Yoshihiko Tanimoto; Minori Ohyama; Erika Ito; Kyoko Akiyoshi; Yuka Onishi; Ai Mori; Ryohei Nomoto (BMC Research Notes)
Abstract Background Human adenoviruses (HAdVs) cause various diseases, and they frequently undergo recombination. As adenoviruses are susceptible to recombination, whole-genome sequencing and analysis are essential approaches to understanding viral properties. In the present study, we performed whole-genome sequencing to characterize adenoviruses and assess the local epidemic genotypes of adenovirus-related diseases in Kobe, Japan. Methods Eighty HAdV cell culture-positive strains isolated from clinical specimens in Kobe City, Japan, between 2018 and 2022 were used. Whole-genome sequencing, phylogenetic analysis, and recombination analysis were performed. Results Disease-specific HAdV species were detected, with species B and C being the primary species detected for pharyngoconjunctival fever and species F for infectious gastroenteritis. All species B strains belonged to the HAdV-3 genotype. Multiple genotypes were detected in species C, including five strains in which the new genotype, P85H5F5, was identified in pharyngoconjunctival fever specimens. Conclusions Whole-genome analysis of HAdV is an important approach not only for understanding local epidemics, but also for monitoring the emergence of recombinant genotypes.